Predictors of the usage of contraceptive implants among women of reproductive age in Ondo State, Southwest Nigeria (2020)
Background: A major characteristic of all developing countries is rapid population growth which is due to high fertility, birth rates and poor utilization of contraceptive methods. This study therefore assessed the predictors of contraceptive implants utilization among women of reproductive age in Ondo State, Nigeria. Methods: A descriptive cross-sectional study design was used and a total of 230 women were selected by multi-stage sampling technique. Questionnaire administration was interviewer-based majority of the women could not read. Data analysis was con- ducted using SPSS version 23. Research questions and hypotheses were answered and tested with descriptive statistics (frequency, percentages), chi-square test of significance and binary logistic regression. Levels of significance was set at p ≤ 0.05. Results: The prevalence of contraceptive utilization (any method) and contraceptive implant utilization were 92.2% and 31.1% respectively. Variables such as education (72= 6.91, p = 0.03) and lack of counseling from providers (72 5.05, p = 0.03) were significantly associated with the utilization of contraceptive implant. These two variables were also the predictors of contraceptive implant utilization. Women with secondary and tertiary education have higher odds of utilizing contraceptive implants (OR = 1.21, 95% CI = 1.01-7.82, p = 0.04) and (OR = 2.53, 95% CI = 1.49-11.47, p = 0.03) compared to women who had primary or no education while those who claimed to be adequately counseled by providers are about two times more likely to use contraceptive implants (OR = 2.33, 95% CI = 1.08-5.51) Conclusion: This study showed the important role of education and health workers in providing information about contraceptive implants. Therefore, health workers' knowledge of family planning counseling and services should be constantly upgraded so as to improve their roles in educating, mobilizing, counseling the women regarding contraceptive implant insertion.